Numerical Analysis of J-Hook Connectors’ Effect on the Performance of Steel-Concrete Composite Shear Walls - Seyed Mohammad Farnam; Mohsen Khorshidi (Journal of Rehabilitation in Civil Engineering)
The use of shear walls is one of the diverse approaches to deal with lateral forces, and composite shear walls are among the different types of these walls. Composite walls consist of two steel sheets and a concrete core between them joined by shear connectors. In this system, the concrete cover can also participate in the load-bearing of the section. Shear connectors are used for bonding concrete to the steel sheet in the wall. Due to the necessity of creating a composite functionality, these connectors play an important role in the behavior of the system. Moreover, the effect of J-hook connectors on steel-concrete composite shear walls is investigated. For this aim, an experimental model is simulated and validated in the ABAQUS software. After verifying the accuracy of the model, a parametric analysis is defined and further studies are performed by using a nonlinear in-crescent static method (pushover method). The results of this study show that the J-Hook connector positively affects increasing load capacity and reducing the out-of-plane displacement of the composite shear wall. Additionally, the number and location of the connectors have a great impact on the both load and buckling capacity of the steel plate. Above all, adding concrete to the steel shear wall which consists of two steel sheets, not only rise the wall's bearing capacity by 14 percent, but improve the performance of the interaction between materials by about 17%.